Transient ablation of alveolar macrophages leads to massive pathology of influenza infection without affecting cellular adaptive immunity - Purnama, Christina (2014)
Alveolar macrophages (AMs), localized at the pulmonary air-tissue interface, are one of the first lines of defense that interact with inhaled airborne pathogens such as influenza viruses. By using a new CD169-DTR transgenic mouse strain we demonstrate that specific and highly controlled in vivo ablation of this myeloid cell subset leads to severe impairment of the innate, but not adaptive, immune responses and critically affects the progression of the disease. In fact, AM-ablated mice, infected with a normally sublethal dose of PR8 influenza virus, showed dramatically increased virus load in the lungs, severe airway inflammation, pulmonary edema and vascular leakage, which caused the death of the infected animals. Our data highlight the possibilities for new therapeutic strategies focusing on modulation of AMs, which may efficiently boost innate responses to influenza infections.